Improving Graduate Employability by Implementing Subject Benchmarks. - Beck, Wendy; Smith, Claire; Sinclair, Anthony (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at the University of New England. This Fellowship explored archaeology subject benchmarks in Australia and the relationship between standards and graduate employability. The report outlines key findings from the data collection and interviews undertaken for this program. It identifies enablers and barriers to benchmarking and implementing professional standards, incorporating the suggestions of workshop participants. The report concludes with a summary that highlights program features that could be extended to encourage standards in the Humanities and Social Sciences.